The COVID-19 Pandemic: What Factors can Affect BUMN-20 Stock Return in Indonesia? - Nur Afnila Audy; Harunnurrasyid Harunnurrasyid; Sri Andaiyani (Department of Development Economics, Universitas Sriwijaya, 2022)
The purpose of this study is to analyze the effect of the policy rate, inflation, exchange rate, and world oil prices on the stock return of 20 companies listed on the State-Owned Enterprises of Indonesia (BUMN-20) Index from July 2016 to June 2021. We divided into three periods that are all periods, before and during pandemic COVID-19. The population in this study is companies listed on Indonesia Stock Exchange (IDX). The sample is determined by using purposive sampling with a total amount of 20 companies and total data is 846. This study used quantitative data analysis in the form of time-series data and documenting methods in obtaining the data. The analytical tools in this study are using multiple regression analysis. The result shows that the policy rate has a significant positive effect on stock returns, inflation and exchange rate have a significant negative effect on stock returns, and world oil prices do not appear any significant effect on the stock return of the BUMN-20 Index. While before and during the COVID-19 pandemic imply only an exchange rate that has a significant and negative effect on stock return. This implies that the COVID-19 pandemic does not appear a significant effect on the performance of BUMN-20 return.